Andina Magazine No. 9 - César Leonardo Munive Carrión (2024)
This issue of Andina magazine explores the culture of peace in the face of regional crises marked by violence and impunity. It examines education as a catalyst for change and analyzes security policies within the Andean Community in response to organized crime. The content includes reflections on gender, the aesthetics of drug trafficking, and critical discourse, fostering a space for scientific and interdisciplinary debate.
Keywords: Cultura of Peace; Education; Security; Justice; Human Rights